2020
DOI: 10.1002/ijc.33328
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption, cigarette smoking and cancer of unknown primary risk: Results from the Netherlands Cohort Study

Abstract: Cancer of unknown primary (CUP) is a metastasised malignancy with no identifiable primary tumour origin. Despite the frequent occurrence and bleak prognosis of CUP, research into its aetiology is scarce. Our study investigates alcohol consumption, tobacco smoking and CUP risk. We used data from the Netherlands Cohort Study, a cohort that includes 120 852 participants aged 55 to 69 years, who completed a self‐administered questionnaire on cancer risk factors at baseline. Cancer follow‐up was established through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Age, sex, smoking and alcohol consumption were considered as predefined confounders and were used in all statistical models, as these factors have been demonstrated to be associated with CUP (K. Hemminki, Chen, et al, 2015;Hermans et al, 2021;Kaaks et al, 2014;Vajdic et al, 2019). Potential confounders (BMI, socio-economic status, physical activity and diabetes status) were evaluated using the backward elimination procedure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Age, sex, smoking and alcohol consumption were considered as predefined confounders and were used in all statistical models, as these factors have been demonstrated to be associated with CUP (K. Hemminki, Chen, et al, 2015;Hermans et al, 2021;Kaaks et al, 2014;Vajdic et al, 2019). Potential confounders (BMI, socio-economic status, physical activity and diabetes status) were evaluated using the backward elimination procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, modifiable lifestyle-related risk factors have been highlighted as influential. For instance, CUP is associated with cigarette smoking (K. Hemminki, Chen, et al, 2015;Hermans et al, 2021;Kaaks et al, 2014;Vajdic et al, 2019). Similarly, alcohol consumption is also associated with CUP risk in a dose-response relationship (Hermans et al, 2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…By assessing lifestyle factors that are potentially 1 3 associated with the disease, however, it may be possible to prevent future CUP patients. Certain modifiable risk factors, such as cigarette smoking and alcohol consumption, have been linked to the development of CUP [9][10][11][12]. Nonetheless, the relationship between diet and CUP has been less well studied, and that is particularly true with respect to meat consumption [11].…”
Section: Introductionmentioning
confidence: 99%
“… 1 Alcohol consumption and cigarette smoking have a correlation with increasing CUP risk. 2 CUP accounts for approximately 2–5% of all new tumors. 3 In a previous study, CUP was diagnosed as a malignant tumor and metastasis was confirmed through histology.…”
Section: Introductionmentioning
confidence: 99%